Antecedents and consequences of the complementarities between green operations management practices: an empirical investigation in Oman - Al Sheyadi, Anwar (2014)
Green Operations Management (GOM) is becoming an increasingly important element in the strategic agenda of many enterprises. Its main aim is to enhance the ability of an enterprise to address stakeholder environmental concerns throughout the entire product life cycle (PLC). Earlier studies have recognized GOM as a useful tool to improve competitiveness (Zhang et al ., 2008; Sarkis et al., 2010) and business performance (Kassinis and Vafeas, 2006; Jacobs et al., 2010; Zhu et al., 2012) Over the last few decades, the role of environmental management in achieving sustainable economic development is attracting growing global attention both theoretically and empirically. GOM is particularly important for enhancing the attractiveness of manufacturing companies of less developed countries such as Oman, to be selected as a partner in the global supply chain network of multi-national companies. However, there is a lack of integrative empirical studies to link and simultaneously examine the interrelationships between environmental drivers, practices and performance of manufacturing firms in general and within the context of less developed countries in particular. Through a review of the GOM and strategic environmental management literature, several unexplored areas were identified which are related to: a) The need for empirical studies to conceptualise various types of environmental practices as complementary to each other. Complementarity of GOM practices refers here to the combined sum of the effects of different sets of GOM practices being greater together than individually. b) The need for empirical studies to examine the influence of two distinct groups of stakeholders (i.e. market and non-market stakeholders) on the adoption of GOM practices. c) The need for empirical studies to examine whether the relationship between stakeholder pressures and the adoption of GOM practices is mediated by an organisation’s internal capabilities such as the development of environmental cross-functional collaboration (CFC). CFC is here defined as the extent of intra-organisational collaboration, interaction and integration of various core functional areas within the firm on environmentally significant issues (Auh and Menguc, 2005). d) The need for empirical studies investigating whether this mediated effect of CFC holds across firms regardless of their size, level of pollution intensity and degree of international orientation. e) The need for empirical studies examining whether environmental performance is considered as a mediator on the relationships between GOM practices and organisational savings and spending, where organisational savings and spending respectively reflect the saving advantages and increase in overall spending resulting from the adoption of GOM practices. This research is explanatory, deductive in nature, and underpinned mainly by a quantitative research design that was supplemented by document analysis of environmental strategies and performance and some qualitative semi-structured interviews with managers of five Omani manufacturing firms. To achieve the objectives of this research, an integrated conceptual framework was developed and set of hypotheses were proposed. The analysis of the survey data collected from 138 Omani manufacturing firms was conducted using structural equation modelling. In this research, empirical support was found for most of the research hypotheses, generally revealing that pressures from both market and non-market stakeholders can influence the adoption of GOM practices and that adoption of GOM practices can influence organisational business benefits, spending and environmental performance. However, the relationship between the adoption of GOM practices and organisational business benefits was found to be further mediated by the level of environmental performance. Moreover, by integrating four distinct, yet interrelated sets, of environmental practices into a second order factor/construct called ‘collective GOM competency’, this research found empirical evidence for the superiority of the second order construct in explaining the relationships between the antecedents and consequences of the adoption of environmental practices. Furthermore, the mediation effect of CFC on the relationship between stakeholder pressures and the adoption of environmental practices was empirically confirmed. This mediation effect of CFC was found to be significantly stronger only for the case of highly internationalised firms compared to their counterparts. Hence, firm characteristics are not always considered as moderators on the relationship between CFC and the adoption of GOM practices. The findings of this study provide new directions for future research and new theoretical and practical insights in GOM practices in manufacturing firms.